ChemInform Abstract: The Search for Room Temperature Tetragonal Phases of Fe—Mn—Ga: A Reactive Crucible Melting Approach. Issue 36 (August 2016) - Ener, Semih; Kroder, Johannes; Skokov, Konstantin P.; Gutfleisch, Oliver
Abstract: The reactive crucible melting technique is used as a rapid bulk screening method in the search for new permanent magnetic materials.